The Study of the Effectiveness of Engklek Game in Vocabulary Learning at Primary Schools in Mojokerto - Nuril Badiatus Sa’adah; Nurhayati Ganinda; Wiwik Mardiana (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to measure the effectiveness of using the traditional game "engklek" for teaching English vocabulary mastery of grade 6 students at SDN Mlaten, Mojokerto. This research used a quantitative approach with a one group pretest-posttest design. The research sample consisted of students in grades 6A and 6B at SDN Mlaten. Data was collected through pretest and posttest to measure students' vocabulary mastery before and after intervention. Data analysis was conducted using paired t-test statistical test to determine the significance of the value results. The results showed that there was a significant change in students' English vocabulary mastery after participating in learning using the traditional game "engklek". The average score of the pretest was 56.73 and the average score of the posttest was 82.65. The test carried out also produced positive results because the sig level. is below or less than alpha (0.00 < 0.05). This has implications for rejecting the null hypothesis (H0) and accepting the alternative hypothesis (Ha). The use of the traditional game "engklek" has proven effective for teaching English vocabulary mastery at primary school.